Knowledge in the policy process: a case study of the language-in-education policy in Malaysia / Zuraidah Zaaba...[et al.] - Zaaba, Zuraidah; Mahmoud Ramadan, Farida Ibrahim; Gunggut, Haijon; Anthony Aning, Ibianaflorinciliana Niane; Umemoto, Katsuhiro (2010)
This case study examines the language-in-education policy in Malaysia in the context of teaching science and technology in English at higher education institutions. The language-in-education policy of teaching science and technology in English was initiated in 1993 at higher education institutions and extended to the primary and secondary levels in 2003. In 2009, however, the government announced that English for science and mathematics in the primary and secondary levels will gradually be phased out by 2012. This study focuses on the knowledge shared, utilized and created by policy makers during the policy-making process, in particular the agenda-setting and formulation stages. Our review of the relevant literature suggests that knowledge shared, utilized and created by policy makers in Malaysia is strongly influenced by the highly- centralized and bureaucratic top-down system. Different policy makers are influenced by their beliefs and values, and by various prominent individuals with competing ideologies and long-standing practices. Because the policy environment in Malaysia is highly centralized, a new idea must go through a complicated process of exchange and selection before it spreads through the policy environment, gets accepted by policy makers, and becomes part of an institutional agenda.